Will Formalities during the Pandemic: A Comparative Study of Malaysia and Selected Jurisdictions - Gary Kit Min Ng; Chee Ying Kuek; Eng Siang Tay; Francesca Nyuk Oi Chin; Joanne En Ling Lau (Hasanuddin Law Review, 2022)
Most countries around the world have entered the endemic stage of the novel coronavirus after 2 years of battling with the soaring rise of infections among the people. As of 1 April 2022, Malaysia, a country which has one of the highest rates of infection per capita in Southeast Asia, has entered the endemic phase of Covid-19. For a will to be valid in Malaysia, the formalities in the Wills Act 1959 (Revised 1998) must be strictly conformed to. A slight deviation from the formalities would render invalid the will that conveys the testamentary intention of the testator. The Covid-19 pandemic has raised several issues including issue of mobility, making wills difficult to be validly executed in accordance with the Wills Act 1959. Even though Malaysia has moved on to the endemic stage, the pandemic of Covid-19 has clearly shown the inadequacy of Wills Act 1959 to serve in the changed and ever-changing world. This paper adopts the doctrinal legal research method by analysing the existing laws in Malaysia and comparing with other jurisdictions such as Australia, United Kingdom, and the United States of America, in considering the necessary reforms in order to uphold the testamentary intention of the will despite the need for formalities, to cope with future unprecedented events. This includes allowing remote execution, adopting electronic wills and electronic signatures in the execution of wills, and introducing dispensing powers. Reforms to the Wills Act are necessary due to the challenges encountered in the new norm and also in light of the rapid technological advancements that the world has undergone.